Teamwork what must go right, what can go wrong - Larson, Carl E.; La Fasto, Frank M. (Sage series in interpersonal communication, 1989)
What are the secrets of successful teams? Why do some teams achieve remarkable success while others fail or are consigned to mediocrity? To find the answers, Carl E. Larson and Frank M. J. LaFasto conducted a three-year study of teams and team achievement. Interviewing a wide range of teams, including the space shuttle Challenger investigation team, executive management teams and a championship football team, Larson and LaFasto discovered a surprising consistency in the characteristics of effective teams. In Teamwork, they explore the eight properties of successful teams: a clear, elevating goal; a results-driven structure; competent team members; unified commitment; collaborative climate; standards of excellence; external support and recognition; and principled leadership. A final chapter examines the priority of the steps that lead to the building of a high performance team. The authors strive to make the concepts concrete, coupling solid theory with straightforward, practical advice on how to apply it and with lively, fascinating anecdotes. The volume will appeal to practitioners, scholars, and advanced students in the areas of organization studies and management, as well as interpersonal communication.